The transfer of corruptive routines from old industrial regions to innovation clusters: a blind spot in innovation studies - Christiane Gebhardt (Triple Helix, 2017)
How innovation programs fail and innovation networks deviate from legal paths is a problem not yet fully understood. The complex interdependence between blockages of innovation and organizational corruption is a novel field of research in innovation studies. Equally, traditional approaches to explain opportunity-driven criminal behavior of individuals fail to explicate organizationally driven routines, and the rise of corruption despite anti-corruption campaigns remains a problem which is still unaddressed. This results in a mismatch with the increasing importance of addressing the issue of corruption. To contribute towards closing this gap, we examine, using the sociological concept of organizational deviance, the phenomenon of corruption in innovation clusters. A recent wave of corruption cases in China confirms the need for research in this area in relation to organizational role models for the transformation of mature industries and lagging regions. We discuss the potential danger of a transfer to Triple Helix-based constellations in innovation of routines found in corrupt systems that are impeding foreign direct investments and effective regional growth. The findings are based on a secondary analysis of the transformation of the Chinese coal-mining sector, a sector in which there is strong evidence of corrupt behavior and which is also a key target for politically induced transformation and modernization. The study demonstrates the importance of a consideration of organizational development in Triple Helix constellations and supports arguments in favor of good cluster governance in Triple Helix-based regional innovation systems.
Keywords: 330; Anti-corruption; China; Coal-mining sector; Corrupt systems; Corruption; Decentralization; Fast-growing economies; Good cluster governance; Innovation policy; Modernization; Organizational deviance; Transformation; Triple Helix-based regional innovation systems